Occult small bowel adenocarcinoma in Crohn’s disease-more than a simple stricture - Marques, Carolina; Ferreira, Cátia; Pereira, Ricardo Vaz; Guidi, Gonçalo; Pinto-de-Sousa, João (International Surgery Journal, 2024)
Small-bowel adenocarcinoma (SBA) accounts for less than 5% of all gastrointestinal cancers. It is generally linked to genetic disorders and immune-mediated inflammatory conditions like Crohn’s disease (CD). Despite advances in oncology, SBA has a poor prognosis and high relative risk in this subgroup of patients. Risk factors for the development of SBA in patients with CD include a stricture phenotype and a long- standing disease. This article aims to expose a case of association between CD and SBA and its management. A 66-year-old woman with long-standing terminally ileum-affected CD with multiple admissions due to sub-occlusive episodes and weight loss. CT and MRI revealed intestinal thickening in the small bowel, suggesting an inflammatory stenosis and entero-enteric fistulous tracts. An ileocolectomy was performed, and the patient’s histopathological evaluation revealed a mucinous invasive adenocarcinoma of the terminal ileum. The patient was treated with adjuvant chemotherapy and has been under surveillance for two years, without malignant recurrence. Although it is a relatively rare neoplasm, CD patients have a significant risk of developing SBA, when compared to the general population. Diagnosis is challenging due to the occult nature of CD-associated SBA, and imaging and endoscopy alone make it difficult to detect the pathology. Treatment involves a high index of suspicion for the diagnosis and a balance between extended mesenteric resection and CD surgery’s primary idea of bowel length preservation. Despite recent advances in oncology, the survival rate in CD-SBA patients remains low. Long-standing CD patients should have the terminal ileum monitored regularly and surgeons should be aware for occult SBA. Post-resection patient surveillance involves regular abdominal exams, serial surveillance, cross-sectional imaging, and monitoring for obstructive symptom recurrence. There is a lack of clear guidelines for primary prevention and surveillance of SBA, with a focus on inflammation management. Preoperative diagnosis techniques are scarce, and patients risk suboptimal treatment if incidental cancer is found. Strategies include right mesenteric-based surgical techniques and/or frozen section exam, always balancing cancer treatment and bowel preservation which is of high relevance in this subgroup of patients.